PENGARUH PERSISTENSI LABA, INVESTMENT OPPORTUNITY SET, DAN STRUKTUR MODAL TERHADAP KUALITAS LABA PADA PERUSAHAAN SEKTOR FOOD AND BEVEREGAE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kristy, Fiona; Widyastuti, Tri; Maidani, Maidani; Sari, Pratiwi Nila (LPPM Institut Pendidikan Nusantara Global, 2024)
The purpose of this study is to test and analyze the effect of Earnings Persistence, Investment Opportunity Set ̧ and Capital Structure on Earnings Quality directly or through earnings quality variables. Quantitative research method, with the type of secondary data source obtained from the company's annual financial statements and sampling techniques using purposive sampling. The population in this study is food and beverage sector companies in 2019-2022 with a total population of 88 companies. The results of this study show that Earnings Persistence has no effect Earnings Quality, Investment Opportunity Set has a positive effect on Earnings Quality, Capital Structure has a positive effect on Earnings Quality, and Profit Persistence, Investment Opportunity Set, and Capital Structure simultaneously effect Earnings Quality.